FROM REACTIVE TO PROACTIVE: HOW COVID-19 TRANSFORMED CONSUMER BEHAVIOR IN HEALTH INSURANCE MARKETS - Kondapally, Chyavana; Reddy, M Vikram; Kumar, B. Mohan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The COVID-19 pandemic has fundamentally changed the consumer behavior worldwide, they affect every industry and healthcare insurance industry is no exception. From the given scenario, this paper discusses how the pandemic played its role in changing consumer attitudes and behaviors regarding the health insurance domain from being post-symptomatic to pre-symptomatic. Before the outbreak of the pandemic, most consumers still saw health insurance as an additional product, which was only desirable during sick or emergencies. Though the idea was slightly promoted prior to the health crisis, the consumers made a massive shift of playing an active role in demanding coverage and policy explanations. The potential drivers for this change are addressed in the study, such as enhanced health consciousness, the risk of growing costs of healthcare and the necessity to prepare for an unpredictable healthcare future. Based on the results of the surveys and the interviews with the consumers, insurance providers, and other industry gurus, this paper seek to assess the changes in the consumer decision making process with particular focus on the value of the health insurance during the pandemic period. Moreover, it explores the ways through which the availability of the insurance products and services can be boosted through digital technology platforms. The study also shows that COVID-19 has not only fast-forwarded this change but has also altered the future behavior of consumers- with a focus towards health insurance, preventive health measures, and financial vulnerability. Thus, this paper fills a gap in the existing literature concerning the phenomenon of crises and how they may reconfigure consumer markets with a relevance in fields of health and financial solutions.